Fungal photobiology: a synopsis - L.M. Corrochano (IMA Fungus)
Fungi respond and adapt to many environmental signals including light. The photobiology of fungi has been extensively investigated, but in recent years the identification of the first fungal photoreceptor, WC-1 in the ascomycete Neurospora erassa, and the discovery that similar photoreceptors are required for photoreception in other ascomycete, basidiomycete and zygomycete fungi has allowed the molecular characterization of light reception and the early steps of signal transduction in a number of model fungi. This contribution is based on presentations made at the Special Interest Group Meeting on "Fungal Photobiology" held during IMC9. The contributions summarize the current status of fungal photobiology in Aspergillus nidulans, Neurospora erassa, Mucor eireinelloides, and Coprinopsis cinerea.